Inverse Opal Photonic Gel Containing Charge Stabilized Boronate Anions for Glucose Sensing at Physiological pH (Phys. Status Solidi RRL 2/2019). Issue 2 (8th February 2019) - Kim, Dongyoun; Koh, Young Gook; Lee, Wonmok
Abstract : The cover picture describes an inverse opal photonic gel (IOPG) sensor exhibiting the structural color change by Bragg diffraction of light when glucose binds to phenylboronate group within IOPG which is stabilized by neighboring trimethylamino group. Formation of 2:1 boronate–glucose complex results in a shrinkage of IOPG, subsequently changing the structural color from red to green. Such glucose‐sensing IOPG was fabricated and studied by Wonmok Lee and coworkers, as reported in article no.1800416 . This article belongs to a group of 5 contributions on ‼Green Photonics‽ assembled in this issue.